INFLUENC OF IRRIGATION PERIODS AND ORGANIC FERTILIZER ON SOIL PHYSICAL CHARACTERIZATION UNDER THE SYSTEM OF RICE INTENSIFICATION (SRI) - & Al-Maadhedi, Al-Hasanie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field trial was conducted at Al-Mishkhab Rice Research Station at Najaf province during 2015 rice season to assess the effects of irrigation periods and organic manure on soil physical properties under System of Rice Intensification The experiment was conducted using split split plot arrangement with RCBD design with three replicates. The main plots were irrigation schedule where practiced: daily and intermittent water application where irrigation water was at two different intervals 3, 5 day. The sub plots were varieties (anber33,jasmin) and three amount of organic manures 0, 5, 10 ton.haˉ¹, planted under System of Rice Intensification (SRI) compared with conventional method. The results indicated that superiority of irrigation interval 3 day treatment with 10 ton.haˉ¹ In the attribute of soil density and total soil porosity, as this treatment gave the average in the bulk density 1.24 Mg m-3 compare with fertilization treatment with irrigation 3 days intervals, which gave an average of less than 1.39 Mg m-3, as well as the treatment excelled in the total porosity of the soil as it gave the highest average 50.18 %, while the comparison gave the lowest percentage of soil aggregate reached 13.00 %. In irrigation 3 days interval and 10 ton.haˉ¹ of organic matter led to increased values of available water to 0.331 cm3.cm -3 compared with a sample before planting, which gave an average of less than 0.193 cm3.cm-3. Given the treatment of interaction between the irrigation 3 days intervals and fertilization treatment recorded the lowest average porosity 48.13 %. The high percentage of soil aggregates, was with the treatment irrigation 3 days interval on the highest average rate of 57.00 % compared with the comparison treatment fertilization and daily irrigation, which 10 ton.haˉ¹ quantities highest average for the hydraulic conductivity reached 0.1320 cm . min-1 compared with the treatment of fertilizing comparison and irrigation daily which gave the lowest average saturated hydraulic conductivity reached 0.0577 cm . min-1.